Experiences of Canadian perinatal care during the COVID-19 pandemic: Analysis of open-ended survey responses - Sigourney Shaw-Churchill; Karen P. Phillips (Women's Health)
Background: The COVID-19 pandemic caused significant socioeconomic and healthcare disruptions in Canada. COVID-19 healthcare policies and local infection rates varied considerably across Canada’s geographically diverse, multijurisdictional healthcare system. Emergence of highly transmissible COVID-19 variants and widespread COVID-19 vaccination mandates in Fall 2021 further impacted life in Canada. The experiences of pregnant people, in particular, were challenged by COVID-19 outbreaks, Canadian hospital policies, and local public health restrictions. Objective: This study explored experiences of Canadian perinatal care in the context of the COVID-19 pandemic. Design: Online, cross-sectional survey with qualitative analysis. Methods: Individuals pregnant after January 1, 2020 who received perinatal care in Canada participated in our Pandemic Pregnancy Experiences eSurvey, September 1, 2021 to February 1, 2022. Open-ended survey responses were qualitatively evaluated by thematic and content analysis. Codes were identified both deductively and inductively, categorized using principles of woman-centered care, and developed into major and minor themes. Results: Prenatal care and COVID-19 vaccination experiences were evaluated from 362 participants, with 234 participants also elaborating on their labor and delivery (L&D) care. Major themes organized by woman-centered care category as follows: Choice of Healthcare Provider (good quality healthcare provider, barriers to provider of choice), Autonomy-Healthcare (autonomy empowered, autonomy impacted), Choice of Delivery Place (wanted hospital birth, got hospital birth), Choice of Support Companion(s) (no support companion for prenatal appointments, hospital restrictions L&D support companion(s)), and, Autonomy-COVID-19 Vaccination (vaccinated while pregnant/breastfeeding). Conclusions: Pregnancy and birth experiences were generally positive; however, both COVID-19 and existing constraints of provincial/territorial healthcare systems impacted Canadian perinatal experiences. Limited choice of healthcare provider type and access to prenatal and L&D support companion(s) affected perinatal care satisfaction.